Executive Committee Minutes 2005-11-03 - Academic Senate:::::::::
FSAC's response to Personal Confidential Information Policy, FSAC response to Background Check Guidelines Policy, Discussion Topic: Steve Orlick's Data, Program Review, Academic Freedom Subcommittee Charge, WASC, Spring Convocation, Faculty Retreat Topic